Composite microwave dielectric ceramic and preparation method thereof

By mixing, granulating and sintering the pre-sintered Mg1.2TiO3.2, SiO2 and Ca0.8Sr0.2TiO3 pre-sintered bodies, a composite microwave dielectric ceramic was prepared, which solved the problems of negative resonance frequency temperature coefficient and high sintering temperature of magnesium titanate ceramics, and achieved the effect of near-zero resonance frequency temperature coefficient and reduced sintering temperature.

CN119859056APending Publication Date: 2025-04-22GUANGZHOU AURORA TECHNOLOGIES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510048731.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The resonant frequency temperature coefficient of magnesium titanate (MgTiO3) ceramics is negative, and the sintering temperature is high when prepared by traditional solid phase reaction method, which limits its practical application.

Method used

Compound microwave dielectric ceramics were prepared by mixing, granulating, pressing and sintering the Mg1.2TiO3.2 presintered body, SiO2 and Ca0.8Sr0.2TiO3 presintered body were mixed, granulated, pressed and sintered, and the sintering temperature was controlled at ≤1300°C, and the generation of microcracks was reduced through the cooling procedure.

Benefits of technology

The resonant frequency temperature coefficient of composite microwave dielectric ceramics is achieved near zero, the sintering temperature is reduced, it is suitable for industrial production, and the dielectric performance with low loss and high quality factors is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859056A_ABST
    Figure CN119859056A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of microwave dielectric ceramics, and particularly relates to a composite microwave dielectric ceramic and a preparation method thereof. The preparation method comprises the following steps: mixing an Mg < 1.2 > TiO < 3.2 > pre-sintered body, SiO2 and a Ca < 0.8 > Sr < 0.2 > TiO < 3 > pre-sintered body to obtain a mixture; sequentially granulating and pressing the mixture to obtain a green body; the green body is sintered, the composite microwave dielectric ceramic is obtained, and the sintering temperature is smaller than or equal to 1300 DEG C. According to the invention, Ca0. 8Sr0. 2TiO3 and Mg1. 2TiO3.2 have opposite temperature coefficients of resonance frequency, so that the temperature coefficient of resonance frequency of the composite microwave dielectric ceramic is close to zero on the premise of maintaining low loss and high quality factor. Meanwhile, by adding the SiO2 component, the sintering temperature of the solid-phase reaction can be effectively reduced, and the method has a wider application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microwave dielectric ceramics, and in particular relates to a composite microwave dielectric ceramic and a preparation method thereof. Background Art

[0002] Microwave dielectric ceramics are a new type of functional electronic ceramics, which refers to ceramics used as dielectric materials in microwave frequency band (mainly UHF and SHF band) circuits and perform one or more functions. It has excellent microwave dielectric properties such as low microwave loss, moderate dielectric constant, and small frequency temperature coefficient. It plays the role of dielectric isolation, dielectric waveguide, and dielectric resonance in microwave circuit systems. It is a key material for microwave components such as dielectric resonators (DR), dielectric filters (DF), dielectric oscillators (DRO), phase shifters, microwave capacitors, and microwave substrates widely used in modern communications. Among them, resonators made of microwave dielectric ceramics have the characteristics of small size, light weight, good temperature stability, and low price compared with metal cavity resonators. They have been widely used in modern microwave communications such as mobile communications, military radars, global satellite positioning systems (GPS), Bluetooth technology, and wireless local area networks (WLAN).

[0003] One of the parameters that characterizes the dielectric properties of microwave dielectric ceramics is the resonant frequency temperature coefficient τ f . Resonance frequency temperature coefficient τ f , also known as temperature drift, is used to characterize the change in the operating frequency of a material when its operating temperature changes. f When it is close to zero, signal delay can be shortened, power loss can be reduced, and temperature stability of microwave circuits can be maintained.

[0004] Magnesium titanate (MgTiO 3 ) ceramics have excellent dielectric properties and are one of the important candidate materials in the field of microwave applications. 3 The resonant frequency temperature coefficient of the ceramic is negative, and the MgTiO 3 The high sintering temperature (1450°C) required for ceramics limits their practical applications. Summary of the invention

[0005] The object of the present invention is to provide a composite microwave dielectric ceramic and a preparation method thereof. The composite microwave dielectric ceramic prepared by the present invention realizes a near-zero resonant frequency temperature coefficient of the composite microwave dielectric ceramic while maintaining low loss and a high quality factor, and at the same time has a low sintering temperature, and has a wider application value.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a composite microwave dielectric ceramic, comprising the following steps:

[0008] Mg 1.2 TiO 3.2 Pre-sintered body, SiO 2 and Ca 0.8 Sr 0.2 TiO 3 The pre-calcined bodies are mixed to obtain a mixed material;

[0009] The mixed material is granulated and pressed in sequence to obtain a green body;

[0010] The green body is sintered to obtain the composite microwave dielectric ceramic, and the sintering temperature is ≤1300°C.

[0011] Preferably, the Mg 1.2 TiO 3.2 Pre-sintered body and Ca 0.8 Sr 0.2 TiO 3 The mass ratio of the pre-sintered body is (81-88): (6-12);

[0012] The Mg 1.2 TiO 3.2 Pre-sintered body and SiO 2 The mass ratio is (81~88):(7~10).

[0013] Preferably, the sintering temperature is 1200-1300°C and the holding time is 3-4h;

[0014] The pressing pressure is 2-3 MPa and the pressing time is 30-60 s.

[0015] Preferably, after the sintering is completed, it also includes: cooling the product obtained by the sintering according to a cooling program to obtain the composite microwave dielectric ceramic; the cooling program includes: cooling from the first temperature to the second temperature according to a first cooling rate, cooling from the second temperature to the third temperature according to a second cooling rate, and cooling from the third temperature to the fourth temperature according to a third cooling rate; the first temperature is 1000-1300°C, the first cooling rate is 1.5-2.5°C / min, the second temperature is 280-1000°C, the second cooling rate is 3-5°C / min, the third temperature is 250-280°C, the third cooling rate is 0.2-0.7°C / min, and the fourth temperature is ≤250°C.

[0016] Preferably, the Mg 1.2 TiO 3.2 The method for preparing the pre-sintered body comprises the following steps:

[0017] Prepare Mg 1.2 TiO 3.2 The raw materials of the pre-sintered body are Mg 1.2 TiO 3.2 The stoichiometric ratio is sequentially pre-mixed, pre-pressed and pre-sintered to obtain the Mg 1.2 TiO 3.2 Pre-sintered body.

[0018] Preferably, the Ca 0.8 Sr 0.2 TiO 3 The method for preparing the calcined body comprises the following steps:

[0019] Prepare Ca 0.8 Sr 0.2 TiO 3 The raw materials of the pre-sintered body are as follows: 0.8 Sr 0.2 TiO 3 The chemical dosage ratio is sequentially pre-mixed, pre-pressed and pre-sintered to obtain the Ca 0.8 Sr 0.2 TiO 3 Pre-sintered body.

[0020] Preferably, the preparation of Mg 1.2 TiO 3.2 The raw materials of the pre-sintered body include magnesium oxide and titanium dioxide; the premixing is wet ball milling; the mass ratio of the material, grinding balls and solvent in the wet ball milling is 1: (3-5): (3-5), and the time of the wet ball milling is 8-12 hours; after the wet ball milling is completed, it also includes: drying and sieving the wet material obtained by the wet ball milling in sequence, and pre-pressing the sieved dry material obtained by the sieving; the drying temperature is 70-90°C, and the time is 8-12 hours; the pre-pressing pressure is 1-5MPa; the pre-sintering temperature is 1000-1200°C, and the insulation time is 2-4 hours.

[0021] Preferably, the preparation of Ca 0.8 Sr 0.2 TiO 3The raw materials of the sintered body include calcium carbonate, strontium carbonate and titanium dioxide; the premixing is wet ball milling; the mass ratio of the material, grinding balls and solvent in the wet ball milling is 1:(3-5):(3-5), and the time of the wet ball milling is 8-12 hours; after the wet ball milling is completed, it also includes: drying and sieving the wet material obtained by the wet ball milling in sequence, and pre-pressing the sieved dry material obtained by the sieving; the drying temperature is 70-90°C, and the time is 8-12 hours; the pre-pressing pressure is 1-5MPa; the pre-sintering temperature is 1000-1200°C, and the insulation time is 2-4 hours.

[0022] The present invention provides a composite microwave dielectric ceramic prepared by the preparation method described in the above technical solution.

[0023] Preferably, the resonant frequency temperature coefficient of the composite microwave dielectric ceramic is +0.6 ppm / °C.

[0024] The present invention provides a method for preparing a composite microwave dielectric ceramic, comprising the following steps: 1.2 TiO 3.2 Pre-sintered body, SiO 2 and Ca 0.8 Sr 0.2 TiO 3 The pre-sintered bodies are mixed to obtain a mixture; the mixture is granulated and pressed in sequence to obtain a green body; the green body is sintered to obtain the composite microwave dielectric ceramic, and the sintering temperature is ≤1300°C. 3 Stoichiometric ratio of MgTiO prepared normally 3 Ceramics usually have a secondary phase of Mg 2 TiO 4 and MgTi 2 O 5 , where MgTiO 3 and Mg 2 TiO 4 The quality factor of MgTi is higher 2 O 5 The dielectric loss of MgTiO is very high, which is an undesirable crystal phase in the preparation process. 3 That is, changing the Mg / Ti ratio, only synthesizing MgTiO with high quality factor 3 Mg 2 TiO 4 The present invention uses non-stoichiometric ratio of Mg 1.2 TiO 3.2 As a component of composite microwave dielectric ceramics, Mg 1.2 TiO 3.2The dielectric constant is between 17 and 18, and the main crystal phase is MgTiO 3 And secondary phase Mg 2 TiO 4 , MgTi-free 2 O 5 The hybrid phase has a higher quality factor and insulation resistance (@1MHz) 10 5 GΩ has better performance. 1.2 TiO 3.2 The resonant frequency temperature coefficient τ f is a negative value, the present invention adopts Ca 0.8 Sr 0.2 TiO 3 Components and Mg 1.2 TiO 3.2 Component compounding, Ca 0.8 Sr 0.2 TiO 3 Ceramics have the properties of high dielectric constant, low dielectric loss and good thermal stability. 0.8 Sr 0.2 TiO 3 Components and Mg 1.2 TiO 3.2 Component compounding, using Ca 0.8 Sr 0.2 TiO 3 With Mg 1.2 TiO 3.2 The two have opposite resonant frequency temperature coefficients, which can enable the composite microwave dielectric ceramic to achieve a resonant frequency temperature coefficient of nearly zero while maintaining low loss and high quality factor. 2 The components can effectively reduce the sintering temperature of the solid phase reaction. Therefore, the composite microwave dielectric ceramic obtained by the preparation method provided by the present invention achieves a near-zero resonant frequency temperature coefficient of the composite microwave dielectric ceramic while maintaining low loss and high quality factor, and the sintering temperature is low, which has a wider application value.

[0025] Further, in the present invention, the Mg 1.2 TiO 3.2 Pre-sintered body and Ca 0.8 Sr 0.2 TiO 3 The mass ratio of the pre-sintered body is (81-88): (6-12). 1.2 TiO 3.2 Pre-sintered body and Ca 0.8 Sr 0.2 TiO 3The mass ratio of pre-sintering can obtain a composite microwave dielectric ceramic with a better resonant frequency temperature coefficient.

[0026] Further, in the present invention, the Mg 1.2 TiO 3.2 Pre-sintered body and SiO 2 The mass ratio of Mg is (81-88): (7-10). 1.2 TiO 3.2 Pre-sintered body and SiO 2 The mass ratio can reduce the sintering temperature of the composite microwave dielectric ceramics without affecting the dielectric properties of the composite microwave dielectric ceramics (including low loss, high quality factor and near-zero temperature coefficient of resonant frequency), making it more suitable for industrial production.

[0027] Furthermore, in the present invention, the sintering temperature is 1200-1300° C. The preparation method provided by the present invention adopts a solid phase reaction method to prepare the composite microwave dielectric ceramic, and the sintering temperature is only 1200-1300° C., which is more suitable for industrial production.

[0028] Furthermore, in the present invention, after the sintering is completed, it also includes: cooling the product obtained by the sintering according to a cooling program to obtain the composite microwave dielectric ceramic; the cooling program includes: cooling from the first temperature to the second temperature according to the first cooling rate, cooling from the second temperature to the third temperature according to the second cooling rate, and cooling from the third temperature to the fourth temperature according to the third cooling rate; the first temperature is 1000-1300°C, the first cooling rate is 1.5-2.5°C / min, the second temperature is 280-1000°C, the second cooling rate is 3-5°C / min, the third temperature is 250-280°C, the third cooling rate is 0.2-0.7°C / min, and the fourth temperature is ≤250°C. The present invention has found that SiO 2 There are many variants, and the mutual transformation between variants is complex and difficult to control, and is often accompanied by large volume changes, resulting in SiO 2 Microcracks will be generated in the ceramic during the sintering process, resulting in poor loss of the composite microwave dielectric ceramic. The present invention further controls the cooling process after sintering so that the SiO 2 Crossing the phase change temperature zone at an appropriate rate can effectively reduce the generation of microcracks in composite microwave dielectric ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The resonant frequency temperature coefficient (τ f ) Change diagram;

[0030] Figure 2 The figure shows the change of the dielectric constant εr of the composite microwave dielectric ceramic prepared in the example. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing a composite microwave dielectric ceramic, comprising the following steps:

[0032] Mg 1.2 TiO 3.2 Pre-sintered body, SiO 2 and Ca 0.8 Sr 0.2 TiO 3 The pre-calcined bodies are mixed to obtain a mixed material;

[0033] The mixed material is granulated and pressed in sequence to obtain a green body;

[0034] The green body is sintered to obtain the composite microwave dielectric ceramic, and the sintering temperature is ≤1300°C.

[0035] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0036] The present invention uses Mg 1.2 TiO 3.2 Pre-sintered body, SiO 2 and Ca 0.8 Sr 0.2 TiO 3 The calcined bodies are mixed to obtain a mixed material. 1.2 TiO 3.2 The method for preparing the pre-sintered body preferably comprises the following steps: preparing Mg 1.2 TiO 3.2 The raw materials of the pre-sintered body are Mg 1.2 TiO 3.2 The stoichiometric ratio is sequentially pre-mixed (hereinafter referred to as the first pre-mixed), pre-pressed (hereinafter referred to as the first pre-pressed) and pre-sintered (hereinafter referred to as the first pre-sintered) to obtain Mg 1.2 TiO 3.2 In the present invention, the preparation of Mg 1.2 TiO 3.2The raw materials of the pre-sintered body preferably include magnesium oxide and titanium dioxide. The purity of the magnesium oxide is preferably ≥99.99%. The purity of the titanium dioxide is preferably ≥99.99%. The first premixing is preferably the first wet ball milling. The grinding balls of the first wet ball milling are preferably zirconium oxide balls. The solvent of the first wet ball milling is preferably anhydrous ethanol. The mass ratio of the material, grinding balls and solvent of the first wet ball milling is preferably 1: (3-5): (3-5), and in the embodiment it can be 1: 5: 3. The time of the first wet ball milling is preferably 8-12 hours, and in the embodiment it can be 9 hours. After the first wet ball milling is completed, the present invention preferably further comprises: sequentially performing the first drying and the first screening on the first wet material obtained by the first wet ball milling, and performing the first pre-pressing on the screened dry material obtained by the first screening. The temperature of the first drying is preferably 70-90° C., and in the embodiment it can be 80° C., and the time is preferably 8-12 hours, and in the embodiment it can be 12 hours. The pressure of the first pre-pressing is preferably 1-5 MPa. The first pre-pressing obtains a block product. The first pre-sintering is performed in a sintering furnace. The temperature of the first pre-sintering is preferably 1000-1200°C, and in the embodiment it can be 1100°C, and the holding time is preferably 2-4h, and in the embodiment it can be 4h. 1.2 TiO 3.2 The raw materials of the pre-sintered body are preliminarily synthesized into the target compound Mg under the temperature conditions of the first pre-sintering. 1.2 TiO 3.2 The first pre-sintering preferably obtains bulk Mg 1.2 TiO 3.2 Pre-sintered body, the present invention preferably comprises the block Mg 1.2 TiO 3.2 The pre-sintered body is crushed and screened in sequence. 1.2 TiO 3.2 There are no special requirements for the specific implementation process of crushing and screening the pre-sintered body.

[0037] In the present invention, the Ca 0.8 Sr 0.2 TiO 3 The method for preparing the calcined body comprises the following steps: preparing Ca 0.8 Sr 0.2 TiO 3 The raw materials of the pre-sintered body are as follows: 0.8 Sr 0.2 TiO 3 The chemical dosage ratio is sequentially pre-mixed (hereinafter referred to as the second pre-mixed), pre-pressed (hereinafter referred to as the second pre-pressed) and pre-sintered (hereinafter referred to as the second pre-sintered) to obtain Ca 0.8 Sr 0.2 TiO3 In the present invention, the preparation of Ca 0.8 Sr 0.2 TiO 3 The raw materials of the sintered body preferably include calcium carbonate, strontium carbonate and titanium dioxide. The purity of the calcium carbonate is preferably ≥99.99%. The purity of the strontium carbonate is preferably ≥99.99%. The purity of the titanium dioxide is preferably ≥99.99%. The second premixing is preferably a second wet ball milling. The grinding balls of the second wet ball milling are preferably zirconium oxide balls. The solvent of the second wet ball milling is preferably anhydrous ethanol. The mass ratio of the material, grinding balls and solvent of the second wet ball milling is preferably 1: (3-5): (3-5), and can be 1: 5: 3 in the embodiment. The time of the second wet ball milling is preferably 8-12 hours, and can be 9 hours in the embodiment. After the second wet ball milling is completed, the present invention preferably further includes: sequentially performing a second drying and a second screening on the second wet material obtained by the second wet ball milling, and performing a second pre-pressing on the screened dry material obtained by the second screening. The temperature of the second drying is preferably 70-90° C., and can be 80° C. in the embodiment, and the time is preferably 8-12 hours, and can be 12 hours in the embodiment. The pressure of the second pre-pressing is preferably 1-5 MPa. The second pre-pressing obtains a block product. The second pre-sintering is performed in a sintering furnace. The temperature of the second pre-sintering is preferably 1000-1200°C, and in the embodiment it can be 1100°C, and the holding time is preferably 2-4 hours, and in the embodiment it can be 4 hours. The second pre-sintering is for the preparation of Ca 0.8 Sr 0.2 TiO 3 The raw materials of the pre-sintered body are preliminarily synthesized into the target compound Ca under the temperature conditions of the second pre-sintering. 0.8 Sr 0.2 TiO 3 The second pre-sintering preferably obtains bulk Ca 0.8 Sr 0.2 TiO 3 Pre-sintered body, the present invention preferably the block Ca 0.8 Sr 0.2 TiO 3 The pre-sintered body is crushed and screened in sequence. 0.8 Sr 0.2 TiO 3 There are no special requirements for the specific implementation process of crushing and screening the pre-sintered body.

[0038] In the present invention, the Mg 1.2 TiO 3.2 Pre-sintered body and Ca 0.8 Sr 0.2 TiO 3The mass ratio of the pre-sintered body is preferably (81-88): (6-12), and in the embodiments, it can be 88:6, 85:8, 83:10 or 81:12. 1.2 TiO 3.2 Pre-sintered body and SiO 2 The mass ratio of is preferably (81-88):(7-10), and in the embodiments it can be 88:10, 85:9, 83:8 or 81:7.

[0039] After obtaining the mixture, the present invention sequentially granulates and presses the mixture to obtain a green body. In the present invention, the granulation process preferably uses a binder, and the binder is preferably polyvinyl alcohol (PVA). The granulation preferably includes the following steps: sequentially subjecting the mixture to a third wet ball milling, a third drying, and a third screening. Obtain a mixed powder; sequentially stir and mix the mixed powder and the binder and perform a fourth screening to obtain a glue-added sieved sample; sequentially subject the glue-added sieved sample to a first pressing, a first crushing, a first grinding, and a fifth screening to obtain a fifth sieved sample; sequentially subject the fifth sieved sample to a second pressing, a second crushing, a second grinding, and a sixth screening to obtain a granulated product. The grinding balls of the third wet ball milling are preferably zirconium oxide balls. The solvent of the third wet ball milling is preferably anhydrous ethanol. The mass ratio of the material, the grinding balls, and the solvent of the third wet ball milling is preferably 1: (3-5): (3-5), and can be 1: 5: 3 in the embodiment. The time of the third wet ball milling is preferably 6-8 hours, and can be 8 hours in the embodiment. After the third wet ball milling is completed, the present invention preferably further comprises: performing a third drying and a third screening on the third wet material obtained by the third wet ball milling in sequence. The temperature of the third drying is preferably 70-90°C, and can be 80°C in the embodiment, and the time is preferably 8-12h, and can be 12h in the embodiment. The third screening preferably uses a 100-mesh screen. The binder is preferably polyvinyl alcohol (PVA). The present invention has no special requirements on the amount of the binder, as long as the granulation is carried out smoothly. The fourth screening preferably uses an 80-mesh screen. The first pressing preferably places the glue-added sieved sample in a mold. The pressure of the first pressing is preferably 1-5MPa, and can be 5MPa in the embodiment, and the time is preferably 10-20s. The fifth screening preferably uses a 60-mesh screen. The second pressing preferably places the glue-added sieved sample in a mold. The pressure of the second pressing is preferably 5-10MPa, and the time is preferably 10-20s. The sixth screening preferably uses a 60-mesh screen.

[0040] In the present invention, the pressing is preferably carried out by placing the granulated product obtained by the granulation in a mold. The diameter of the mold is preferably 10 mm. The pressure of the pressing is preferably 2 to 3 MPa, and the time is preferably 30 to 60 seconds. The shape of the green body is cylindrical, and the bottom diameter of the green body is preferably 10 mm, and the thickness is preferably 5 mm.

[0041] After obtaining the green body, the present invention sintered the green body to obtain the composite microwave dielectric ceramic, and the sintering temperature is ≤1300°C. In the present invention, the sintering temperature is preferably 1200-1300°C, and the holding time is preferably 3-4h. In the present invention, the purpose of sintering is to transform the formed green body material into a composite microwave dielectric ceramic material with good density, certain strength and characteristics. The binder is removed during the sintering process.

[0042] In the present invention, after the sintering is completed, the present invention preferably further comprises: cooling the product obtained by the sintering according to a cooling program to obtain the composite microwave dielectric ceramic. The cooling program preferably comprises: cooling from the first temperature to the second temperature according to the first cooling rate, cooling from the second temperature to the third temperature according to the second cooling rate, and cooling from the third temperature to the fourth temperature according to the third cooling rate. The first temperature is preferably 1000-1300°C, more preferably 1200-1300°C. The first temperature is preferably the same as the sintering temperature. The first cooling rate is preferably 1.5-2.5°C / min, more preferably 1.8-2.3°C / min, and can be 2°C / min in the embodiment. The second temperature is preferably 280-1000°C, more preferably 300-900°C, further preferably 350-800°C, and can be 1000°C in the embodiment. The second cooling rate is preferably 3-5°C / min, more preferably 3.5-4.5°C / min, and can be 4°C / min in the embodiment. The third temperature is preferably 250-280°C. The third cooling rate is preferably 0.2-0.7°C / min, more preferably 0.3-0.6°C / min, and in the embodiment it can be 0.5°C / min. The fourth temperature is preferably ≤250°C, more preferably 200-250°C, and in the embodiment it can be 250°C. In the present invention, after cooling to the fourth temperature, the present invention preferably cools from the fourth temperature to room temperature in a furnace to obtain the composite microwave dielectric ceramic.

[0043] The present invention provides a composite microwave dielectric ceramic prepared by the preparation method described in the above technical solution.

[0044] In the present invention, in the composite microwave dielectric ceramic: the Mg 1.2 TiO 3.2 and Ca 0.8 Sr 0.2 TiO3 The mass ratio of Mg is preferably (81-88): (6-12), and in the embodiments, it can be 88:6, 85:8, 83:10 or 81:12. 1.2 TiO 3.2 and SiO 2 The mass ratio of is preferably (81-88):(7-10), and in the embodiments it can be 88:10, 85:9, 83:8 or 81:7.

[0045] In the present invention, in the composite microwave dielectric ceramic: the Mg 1.2 TiO 3.2 and Ca 0.8 Sr 0.2 TiO 3 The mass ratio is 83:10, and the Mg 1.2 TiO 3.2 and SiO 2 When the mass ratio of is 83:8, the resonant frequency temperature coefficient of the composite microwave dielectric ceramic is +0.6ppm / °C.

[0046] The present invention uses a two-phase composite method to utilize Ca 0.8 Sr 0.2 TiO 3 Regulation of Mg 1.2 TiO 3.2 The dielectric properties of ceramics are improved by adding SiO 2 The sintering temperature is lowered to prepare a composite microwave dielectric ceramic material with an adjustable resonant frequency temperature coefficient close to zero.

[0047] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0048] Example 1

[0049] The present invention provides a composite microwave dielectric ceramic material, comprising the following steps:

[0050] The first step is to follow Mg 1.2 TiO 3.2 The weight of magnesium oxide (purity of 99.99%) and titanium dioxide (purity of 99.99%) was calculated according to the chemical formula, and the weight of each raw material was weighed and placed in a ball mill with zirconium oxide balls and anhydrous ethanol. The weight was added according to the ratio of raw material: ball: anhydrous ethanol = 1:5:3, and the ball milling was mixed and ground for 9 hours. After the ball milling time reached, the material was dried at 80°C and the drying time was 12 hours.

[0051] According to Ca 0.8 Sr 0.2TiO 3 The weight of calcium carbonate (purity of 99.99%), strontium carbonate (purity of 99.99%) and titanium dioxide (purity of 99.99%) were calculated according to the chemical formula, and the weight of each raw material was placed in a ball mill with zirconium oxide balls and anhydrous ethanol, and the weight was added according to the ratio of raw material: ball: anhydrous ethanol = 1:5:3, and the ball milling was mixed and ground for 9 hours. After the ball milling time reached, the material was dried at 80°C and the drying time was 12 hours;

[0052] The second step is to dry the Mg 1.2 TiO 3.2 Raw material samples and Ca 0.8 Sr 0.2 TiO 3 The raw material samples were sieved, pressed into blocks at 5 MPa and placed in a sintering furnace for pre-sintering (pre-synthesis) steps below the sintering temperature. 1.2 TiO 3.2 and Ca 0.8 Sr 0.2 TiO 3 The pre-sintering temperature is 1100℃ and the pre-sintering time is 4h. The main purpose of pre-sintering is to preliminarily synthesize the target compound at a temperature lower than the maximum sintering temperature. 1.2 TiO 3.2 Pre-sintered samples and bulk Ca 0.8 Sr 0.2 TiO 3 Pre-sintered body sample; block Mg 1.2 TiO 3.2 Pre-sintered samples and bulk Ca 0.8 Sr 0.2 TiO 3 The pre-sintered body samples were crushed and sieved, and then Mg 1.2 TiO 3.2 :SiO 2 :Ca 0.8 Sr 0.2 TiO 3 =88:10:6, 85:9:8, 83:8:10, 81:7:12, and mix the ingredients twice.

[0053] The third step is to place the sample with secondary batching in a ball mill with zirconium oxide balls and anhydrous ethanol, and add the raw materials: balls: anhydrous ethanol in a ratio of 1:5:3. The sample is ball milled for 8 hours. After the ball milling is stopped, the material is dried (the drying temperature is 80°C and the drying time is 12 hours) and sieved. The particle size is based on the particle size that can pass through a 100-mesh sieve. The powder after the secondary ball milling is added to the mortar, and the binder (the binder is PVA) is added while stirring until the powder forms pseudo-granules and passes through an 80-mesh sieve; the sample after adding glue and sieving is pressed with a mold at a pressure of 5MPa for 20s, crushed and ground after compaction, and passed through a 60-mesh sieve. After sieving, the sample is pressed with a mold of the same specification at a pressure of 10MPa for 20s, crushed and ground after compaction, and passed through a 60-mesh sieve. Granulation is completed.

[0054] In the fourth step, the granulated powder is filled into a mold with a diameter of 10 mm, and pressed at a pressure of 3 MPa for 60 seconds to form a cylindrical green body with a diameter of 10 mm and a thickness of 5 mm.

[0055] The fifth step is to sinter the pressed green body at 1300℃ and keep it for 3h. The cooling program after sintering is as follows: cool from 1300℃ to 1000℃ at a cooling rate of 2℃ / min, then cool from 1000℃ to 280℃ at a cooling rate of 4℃ / min, then cool from 280℃ to 250℃ at a cooling rate of 0.5℃ / min, and finally cool from 250℃ to room temperature. The mass fraction of Mg can be obtained. 1.2 TiO 3.2 :SiO 2 :Ca 0.8 Sr 0.2 TiO 3 =88:10:6, 85:9:8, 83:8:10, 81:7:12 resonator samples. The purpose of sintering is to transform the formed green material into a material with good density and certain strength and characteristics.

[0056] Step 6: Test the dielectric properties of ceramics: Use 800-grit sandpaper to smooth the upper and lower surfaces of the cylindrical resonator sample prepared by the above formula, measure the size with a vernier caliper, and use a network analyzer equipped with a heating device to measure the relevant dielectric properties and resonant frequency temperature coefficient τ using the parallel plate method. f The test results are as follows: Figure 1 shown.

[0057] Depend on Figure 1 It can be seen that: this embodiment uses Mg 1.2 TiO 3.2 , Ca 0.8 Sr 0.2 TiO 3 The two phases are combined and SiO 2The method of reducing the sintering temperature achieves a near-zero resonant frequency temperature coefficient of the composite microwave dielectric ceramic material while maintaining low loss and high quality factor. The best ratio is the mass ratio of Mg 1.2 TiO 3.2 :SiO 2 :Ca 0.8 Sr 0.2 TiO 3 =83:8:10, the resonant frequency temperature coefficient of the obtained composite microwave dielectric ceramic material is +0.6ppm / ℃.

[0058] Figure 2 The figure shows the change of the dielectric constant εr of the composite microwave dielectric ceramic prepared in the example.

[0059] As can be seen from the above embodiments, the present invention uses Mg 1.2 TiO 3.2 With Ca 0.8 Sr 0.2 TiO 3 Two-phase composite and adding SiO 2 Composite dielectric materials, using Ca 0.8 Sr 0.2 TiO 3 With Mg 1.2 TiO 3.2 The two have opposite resonant frequency temperature coefficients, and a composite material with a resonant frequency temperature coefficient close to zero can be obtained. 2 The sintering temperature can be reduced, and the appropriate cooling rate can be selected during the sintering process to make the SiO 2 The phase change temperature zone is passed at an appropriate rate to reduce the generation of microcracks. The dielectric properties of the composite ceramic provided by the present invention are controlled by the properties of the three starting phases. The present invention can achieve the purpose of preparing a composite microwave dielectric ceramic with a controllable dielectric constant and a near-zero resonant frequency temperature coefficient by changing the content of the three phases.

[0060] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a composite microwave dielectric ceramic, characterized in that: The following steps are involved: Mg 1.2 TiO 3.2 Pre-sintered body, SiO2 and Ca 0.8 Sr 0.2 The TiO3 pre-calcined body is mixed to obtain a mixed material; The mixed material is granulated and pressed in sequence to obtain a green body; The green body is sintered to obtain the composite microwave dielectric ceramic, and the sintering temperature is ≤1300°C.

2. The preparation method according to claim 1, characterized in that: The Mg 1.2 TiO 3.2 Pre-sintered body and Ca 0.8 Sr 0.2 The mass ratio of TiO3 pre-sintered body is (81-88): (6-12); The Mg 1.2 TiO 3.2 The mass ratio of the pre-sintered body to SiO2 is (81-88):(7-10).

3. The preparation method according to claim 1, characterized in that: The sintering temperature is 1200-1300°C and the holding time is 3-4h; The pressing pressure is 2-3 MPa and the pressing time is 30-60 s.

4. The preparation method according to claim 1 or 3, characterized in that: After the sintering is completed, the method further includes: cooling the sintered product according to a cooling program to obtain the composite microwave dielectric ceramic; the cooling program includes: cooling from a first temperature to a second temperature according to a first cooling rate, cooling from the second temperature to a third temperature according to a second cooling rate, and cooling from the third temperature to a fourth temperature according to a third cooling rate; the first temperature is 1000-1300°C, the first cooling rate is 1.5-2.5°C / min, the second temperature is 280-1000°C, the second cooling rate is 3-5°C / min, the third temperature is 250-280°C, the third cooling rate is 0.2-0.7°C / min, and the fourth temperature is ≤250°C.

5. The preparation method according to claim 1, characterized in that: The Mg 1.2 TiO 3.2 The method for preparing the pre-sintered body comprises the following steps: Prepare Mg 1.2 TiO 3.2 The raw materials of the pre-sintered body are Mg 1.2 TiO 3.2 The stoichiometric ratio is sequentially pre-mixed, pre-pressed and pre-sintered to obtain the Mg 1.2 TiO 3.2 Pre-sintered body.

6. The preparation method according to claim 1, characterized in that: The Ca 0.8 Sr 0.2 The preparation method of TiO3 calcined body comprises the following steps: Prepare Ca 0.8 Sr 0.2 The raw materials of TiO3 pre-sintered body are as follows: 0.8 Sr 0.2 The chemical dosage ratio of TiO3 is pre-mixed, pre-pressed and pre-sintered in sequence to obtain the Ca 0.8 Sr 0.2 TiO3 pre-sintered body.

7. The preparation method according to claim 5, characterized in that: The preparation of Mg 1.2 TiO 3.2 The raw materials of the pre-sintered body include magnesium oxide and titanium dioxide; the premixing is wet ball milling; the mass ratio of the material, grinding balls and solvent in the wet ball milling is 1: (3-5): (3-5), and the time of the wet ball milling is 8-12 hours; after the wet ball milling is completed, it also includes: drying and sieving the wet material obtained by the wet ball milling in sequence, and pre-pressing the sieved dry material obtained by the sieving; the drying temperature is 70-90°C, and the time is 8-12 hours; the pre-pressing pressure is 1-5MPa; the pre-sintering temperature is 1000-1200°C, and the insulation time is 2-4 hours.

8. The preparation method according to claim 6, characterized in that: The preparation of Ca 0.8 Sr 0.2 The raw materials of the TiO3 sintered body include calcium carbonate, strontium carbonate and titanium dioxide; the premixing is wet ball milling; the mass ratio of the material, grinding balls and solvent in the wet ball milling is 1:(3-5):(3-5), and the time of the wet ball milling is 8-12 hours; after the wet ball milling is completed, it also includes: drying and sieving the wet material obtained by the wet ball milling in turn, and pre-pressing the sieved dry material obtained by the sieving; the drying temperature is 70-90°C, and the time is 8-12 hours; the pre-pressing pressure is 1-5MPa; the pre-sintering temperature is 1000-1200°C, and the insulation time is 2-4 hours.

9. The composite microwave dielectric ceramic prepared by the preparation method according to any one of claims 1 to 8.

10. The composite microwave dielectric ceramic according to claim 9, characterized in that: The resonant frequency temperature coefficient of the composite microwave dielectric ceramic is +0.6ppm / °C.